Identitas dan Perbedaan Sosial Melalui Pilihan Bahasa dalam Film Hujan Bulan Juni - Arfa Aulia Parinduri; Nayla Lestari; Gressela Sesinta; Ida Basaria (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
This study aims to describe the forms and social functions of code-switching and code-mixing in the film Hujan Bulan Juni and to explain how language choice represents identity and social differences among the characters. The film was chosen because it portrays interactions between characters from different cultural backgrounds Javanese and Manadonese which allows for complex patterns of language contact. The study employed a descriptive qualitative method using observation and note-taking techniques on dialogues containing Indonesian, Javanese, and Manadonese linguistic elements. The data were analyzed using the sociolinguistic frameworks of Gumperz (1982) and Wardhaugh (2015) to uncover the social functions and identity meanings reflected in the speakers’ language choices.The findings reveal that code-switching from Indonesian to Manadonese serves to reinforce ethnic solidarity, emotional closeness, and cultural pride, while switching from Indonesian to Javanese reflects politeness, intimacy, and social hierarchy. Meanwhile, code-mixing between Indonesian and Manadonese marks distinctive speech styles and expresses regional identity, whereas code-mixing between Indonesian and Javanese functions to soften utterances and portray the speakers’ courteous demeanor. Overall, language choice in Hujan Bulan Juni is not merely a communicative tool but also a representation of identity and social differentiation within Indonesia’s multilingual society.